Welfare reform in California : state and county implementation of CalWORKs in the first year - Zellman, Gail (Rand statewide CalWORKs evaluation., 1999)
The California Work Opportunity and Responsibility to Kids (CalWORKs) program is California's response to the welfare reforms Congress set in motion in 1996. The most visible features of this program are its emphasis on moving welfare recipients from reliance on government cash assistance to work and toward self-sufficiency; its use of time limits and participation requirements; its provision of certain services, such as child care and job search assistance, to make participation easier; and its devolution of program authority from the state to the county level. Here, the authors examine the first year of CalWORKs, focusing on the planning and implementation processes and the effects of the program to date. Four themes emerged that will be explored further in future reports: (1) Organizations have changed in response to the expanded mission of CalWORKs, despite limited time for planning. (2) Implementation is under way, but recipient compliance is low. (3) Counties currently have sufficient funds, but this may change. (4) Achieving earnings needed to achieve self-sufficiency before time limits expire is a challenge.